User Engagement against Online Far-Right Actions in Japan: Driven by High Perceptions of Personal Abilities and Benefits - Löschke, Ayaka (Digital Asia, 2022)
This article presents a case study of user engagement against incivility online in Japan, considering three determinants of such engagement identified in a German case study. Japanese users launched the #Internet Rightists Ban Festival in 2018 and are continuing their engagement. As a result, more than 10,500 Twitter accounts have been permanently banned. What drove the participants to initiate and continue their engagement? What type of users attended the festival and led it? This article asks these questions, conducting an inductive qualitative analysis of 3,821 tweets and distinguishing 1,038 participants. It argues that Japanese user engagement has been driven in particular by the perception of personal abilities, such as gaming and comment-writing skills, and the perception of personal benefits, especially from gamification and irony. This article also identifies participants’ left-wing political orientation as an important factor in their continuing sense of responsibility and leadershi
Keywords: flagging; gamification; hate speech; incivility online; irony; Japan; playfulness; user engagement